Model Bisnis Canvas Usaha Pemasaran Cabai Rawit Merah (Studi kasus pada Koperasi Primadona Desa Banyuputih Kecamatan Banyuputih Kabupaten Situbondo) - Mayangsari, Andina; Alfauzi, Farit; Wijaya, Rifky Agnitian; Mufid, Ahmad (Universitas Galuh, 2025)
Primadona Producer Cooperative focuses on the production and marketing of red bird's eye chili and large red chili in Banyuputih District, Situbondo Regency. Unlike savings and loan cooperatives, Primadona is a production cooperative that collects the agricultural products of its members. They act as a direct intermediary between farmers and consumers/markets. Primadona Cooperative has a social function, unlike the negative connotation of a middleman. The focus of this research is the description of the business model of Koperasi Primadona within the 9 elements of the Business Model Canvas. This research uses the Purposive Sampling method, and the data collected from this study consists of primary and secondary data. The research results show that the customer segments of the Cooperative are a segmented market, namely B2C for housewives and B2B for catering, restaurants, kilo kiosks, and traditional markets. Value propositions include the quality of red bird's eye chili and red chili being better compared to other regions. has low shrinkage and good physiological form. Channels use indirect channels through sales, as well as direct channels for information delivery through call centers, social media, bank transfer payments, product delivery through courier services, Customer relationships, in the form of personal assistants with call centers to assist and serve consumers and self-service during the ordering process. Revenue streams are obtained from the sale of red chili peppers and red chilies, as well as self-investment in the form of (initial savings, mandatory savings, reserve funds, and grants) and loan capital. Key resources consist of human resources, warehouse facilities, office, laptops, and agricultural machinery, as well as financial resources in the form of investments and loans. Key activities include activities with fostered farmers and partners, online and offline business activities. Key partnerships consist of alliances with fostered farmers, surrounding farmers, and wholesale markets in Indonesia, coopetition in the middle in Situbondo, and suppliers of fostered farmers and surrounding farmers. Cost structure is a type of cost-driven and consists of expenses at the level of full micro fund partner farmers and cooperatives. This business model generates efficiency but still needs to improve its business activities as well.